Observations and modeling of post-midnight uplifts near the magnetic equator - Nicolls, M. J. (2006)
We report here on post-midnight uplifts near the magnetic equator. We present observational evidence from digital ionosondes in Brazil, a digisonde in Peru, and other measurements at the Jicamarca Radio Observatory that show that these uplifts occur fairly regularly in the post-midnight period, raising the ionosphere by tens of kilometers in the most mild events and by over a hundred kilometers in the most severe events. We show that in general the uplifts are not the result of a zonal electric field reversal, and demonstrate instead that the uplifts occur as the ionospheric response to a decreasing westward electric field in conjunction with sufficient recombination and plasma flux. The decreasing westward electric field may be caused by a change in the wind system related to the midnight pressure bulge, which is associated with the midnight temperature maximum. In order to agree with observations from Jicamarca and Palmas, Brazil, it is shown that there must exist sufficient horizontal plasma flux associated with the pressure bulge. In addition, we show that the uplifts may be correlated with a secondary maximum in the spread-F occurrence rate in the post-midnight period. The uplifts are strongly seasonally dependent, presumably according to the seasonal dependence of the midnight pressure bulge, which leads to the necessary small westward field in the post-midnight period during certain seasons. We also discuss the enhancement of the uplifts associated with increased geomagnetic activity, which may be related to disturbance dynamo winds. Finally, we show that it is possible using simple numerical techniques to estimate the horizontal plasma flux and the vertical drift velocity from electron density measurements in the post-midnight period.